Ethical implications in management of gravely ill children attended in a Pediatric Patient Critical Unit - Pino Armijo, Paola; San Juan Hurtado, Lorena; Monasterio Ocares, María Carolina (Acta Bioethica, 2014)
Aims: To identify the current clinical management of children gravely ill attended in a Pediatric Patient Critical Unit (PPCU), to analyze the ethical implication of management and to propose strategies for the management from a bioethical perspective. Methods: Bibliography revision using data base Medline/Pubmed, Lilacs, ProQuest, Cinhal and SciELO between April and July 2012. For analysis, 29 articles were selected that fulfilled inclusion criteria. Results: Medical advances and the incapacity to recognize and understand death as something natural increasingly make more difficult to establish the limit between a proportionate and disproportionate treatment. With the eagerness of finding a moral framework to facilitate decision making, bioethics —and particularly principle based theory— provides for health care team four principles regulating professional exercise: autonomy, non-maleficence, beneficence and justice. The correct balance among them will allow to provide basic care with responsible ethics. Conclusion: The management of gravely ill children attended at PPCU requires a change in the culture of health care organizations, in which death be viewed as something natural, the importance of decision making after arguing and dialoguing be recognized, considering all stakeholders involved, including nurse professionals in the process, and that it will be possible to recur to a health care ethical committee –competent, interdisciplinary and permanent- when health care team does not arrive to an agreement.